Quality and competence: proposal of an educational model in higher education (2008)
At present, Higher Education is characterized by the tendency of a formation based on competences that guarantees the suitability performance of the graduated on the different felds that they will have to act. Additionally, this academic community has centered its efforts on the search of the quality, demanding an analysis of the criteria associated to this subject, to which must be added the national efforts for education quality assessment.  This horizon, has allowed to Universidad Industrial de Santander to establish a close relationship between the formation based on competences and the quality management, frst of all based, in the necessity to diagnose and to tackle the environment, - understood as the satisfaction of the society in which the graduate acts (users) Whit this refection, the formation is transferred to a context of quality management, requiring a rigorous attention to the appropriateness of the programs and the curricular design (design of the service), the  generation and application of pedagogical strategies (beneft of the service), and the design of standards and assessments tools and evaluation, mainly based on evidences of suitability and performance indicators (analysis, measurement and improvement).